Sharia-based financial literacy acceleration: Strengthening the sakinah family economy in the ‘Aisyiyah Branch Leadership of Ngampilan - Adhianty Nurjanah; Nano Prawoto; Riski Apriliani (Community Empowerment, 2026)
Family financial management is a crucial aspect of realizing a Sakinah family, one that is harmonious, prosperous, and aligned with Islamic principles. However, low financial literacy among women remains a primary challenge hindering household economic stability. This community service program aims to enhance sharia-based financial literacy and management skills among the members of the ‘Aisyiyah Branch Leadership (PCA) in Ngampilan, Yogyakarta. The program was executed in three main stages: 1) socialization of the Sakinah family philosophy, 2) sharia-based family financial management training, and 3) distribution of pocketbook guides as practical references. The evaluation results demonstrated significant success: a 85% increase in participants' awareness of Sakinah family literacy, a 88% improvement in financial management understanding and skills, and 88% of participants validating the pocketbook as highly beneficial. This initiative successfully supports the realization of Sakinah families within PCA Ngampilan while serving as a replicable model for women's empowerment in strengthening household economic resilience.